A política pública de assistência social e a vigilância socioassistencial na fronteira oeste/RS - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present work presents the results and analysis of the data of the research carried out in the municipalities belonging to the Association of Municipalities of the West Frontier of RS (AMFRO), on the implementation and implementation of social assistance surveillance, as part of the Management of the Unified Social Assistance System. The dissertation is the result of the professional master's research of the Graduate Program in Public Policies at Unipampa (PPGPP), and proposes to carry out an analysis on social assistance surveillance on the western border of RS. The research is based on a theoretical reflection on the construction of public and social policies, based on an approach to the contribution of street-level bureaucrats (BNRs) to their implementation. It presents the empirical data collected in eight municipalities belonging to AMFRO, having as research subjects the technicians of SUAS, linked or not to social assistance surveillance. The study proposes to contribute, based on the regulations of the SUAS, to the improvement of the management of the public social policy of social assistance, reflecting on the structuring of the SUAS, the services and management equipment, the objective working conditions and human resources. , contributing to an effective, efficient and effective management of this public policy, in the research territory/region. The research results indicate that there is still no actual implementation of social assistance surveillance in the municipalities belonging to the AMFRO region, which participated in the research. consolidate in the perspective of social protection and defense of rights and citizenship.
Keywords: Política Pública; Assistência Social; Rio Grande do Sul - Fronteira Oeste; Sistema Único de Assistência Social (Brasil); Public Policy; Social assistance; CNPQ::CIENCIAS HUMANAS